Obligate bacterial endosymbionts limit thermal tolerance of insect host species - Zhang, Bo (Proc Natl Acad Sci U S A, 2019)
The thermal tolerance of an organism limits its ecological and geographic ranges and is potentially affected by dependence on temperature-sensitive symbiotic partners. Aphid species vary widely in heat sensitivity, but almost all aphids are dependent on the nutrient-provisioning intracellular bacterium Buchnera, which has evolved with aphids for 100 million years and which has a reduced genome potentially limiting heat tolerance. We addressed whether heat sensitivity of Buchnera underlies variation in thermal tolerance among 5 aphid species. We measured how heat exposure of juvenile aphids affects later survival, maturation time, and fecundity. At one extreme, heat exposure of Aphis gossypii enhanced fecundity and had no effect on the Buchnera titer. In contrast, heat suppressed Buchnera populations in Aphis fabae, which suffered elevated mortality, delayed development and reduced fecundity. Likewise, in Acyrthosiphon kondoi and Acyrthosiphon pisum, heat caused rapid declines in Buchnera numbers, as well as reduced survivorship, development rate, and fecundity. Fecundity following heat exposure is severely decreased by a Buchnera mutation that suppresses the transcriptional response of a gene encoding a small heat shock protein. Similarly, absence of this Buchnera heat shock gene may explain the heat sensitivity of Ap. fabae. Fluorescent in situ hybridization revealed heat-induced deformation and shrinkage of bacteriocytes in heat-sensitive species but not in heat-tolerant species. Sensitive and tolerant species also differed in numbers and transcriptional responses of heat shock genes. These results show that shifts in Buchnera heat sensitivity contribute to host variation in heat tolerance.